INTERDIMENSIONAL RELATIONSHIPS OF TREES IN GREEN AREAS IN CENTRAL CURITIBA, PARANÁ, BRAZIL - Ivasko Júnior, Severo; Biondi, Daniela; Nunho dos Reis, Allan Rodrigo; Behling, Alexandre; Martini, Angeline (Floresta, 2022)
Morphometric analysis of trees can help in the selection of the most suitable species in urban areas, by allowing us to understand the dynamics of tree growth forms. The objective was to develop a morphometric index for trees located in green areas of Curitiba, Paraná. 122 trees of the five species with the highest number of records of fall and removal in Curitiba were selected: Tipuana tipu, Jacaranda mimosifolia, Erythrina falcata, Melia azedarach and Ligustrum lucidum, in the Passeio Público Municipal of Curitiba and in nine squares located in the Centro district. From the biometric data obtained in the field, the Integrated Morphometric Index (IMI) was calculated through multivariate factorial analysis performed in the statistical software IBM SPSS® Statistics. There was low variability between interdimensional sizes, indicating a pattern of growth among species, especially for T. tipu. On the other hand, J. mimosifolia, E. falcata and M. azedarach present greater variability of the morphometric data, with trees of size considerably higher than the average of the others, while L. lucidum was the species with the smallest interdimensional size. The biometric variables total height, crown height, north crown radius, east crown radius and DBH were the most correlated with the tree growth pattern, explaining 57.9% of the data variation. The generated IMI was adequate to evaluate the behavior of the variables, as it explained 72% of the data variation. The T. tipu trees showed the lowest variability between their interdimensional sizes, thus indicating a more evident growth pattern for this species.